Design and characterization of glimepiride hydrotropic solid dispersion to enhance the solubility and dissolution - Lakumalla, Devakamma; Podichety, Neeraja; Maddali, Ravikumar (Creative Pharma Assent, 2024)
Background: Glimepiride lowers blood sugar levels in the body, and treats type 2 diabetes mellitus. But the main problem with the drug is its low aqueous solubility. The primary purpose of this study is to increase its solubility in an aqueous medium by using amphiphilic hydrotropic agents instead of harmful, volatile organic solvents. Methodology: A solubility study of Glimepiride was carried out using various hydrotropic agents at 10%, 20%, 30%, and 40%. In mixed hydrography, 30% of the hydrotropic agents were chosen for making blends due to their highest solubility. The blend's solubility was raised more than 50 times at fixed concentrations of urea (20%) and sodium acetate (10%) in a mixed hydrotropic solution. The solubility of Glimepiride in distilled water is 0.0038 mg/ml; in 30% urea, 49.512 ug/ml; and in 30% sodium acetate, 40.43 ug/ml. The optimized blend prepared hydrotropic solid dispersions by physical mixing and solvent evaporation. It was evaluated for drug content, FTIR, SEM, X-ray diffraction, and in vitro drug release studies. Finally, the drug release profile of the prepared tablet is compared with an already available consumer product. Result: HSD-5 showed an in-vitro drug release of 84.77±0.44 at 90 min, which is higher than the remaining formulations, and no significant change was found in drug content or drug release after 15, 30, and 45 days of stability studies. Scanning electron microscopy (SEM) showed homogenous solid dispersion, crystallinity was determined using X-ray diffraction, and FTIR showed good drug compatibility with carriers. The drug release profile of the prepared tablet was higher than that of the available consumer product. Conclusion: This study revealed that hydrotropic agents can potentially increase glimepiride's solubility and drug release. This approach can effectively enhance the solubility of poorly water-soluble drugs.